A self-tuning PID-based SMES controller by optimal fuzzy gain scheduling for stabilization of inter-area power system oscillation - Chaiyatham, Theerawut; Ngamroo, Issarachai (My University, 2013)
Generally, the PID (Proportional-Integral-Derivative) controller with fixed parameters may fail to provide satisfactory performance when the system nonlinearity is high. To augment the PID control effect, the optimal fuzzy gain scheduling for a self-tuning PID controller (FGS-PID) is presented in this paper. The proposed technique is applied to design an FGS-PID controller of superconducting magnetic energy storage (SMES) for stabilization of inter-area power system oscillation. Without trial and error, the scale factors, membership functions and control rules of the FGS-PID controller are automatically tuned by a bee colony optimization. With the optimal FGS-PID controller, the PID parameters can be adjusted automatically according to various system operating conditions. As a result, the high robustness of the FGS-PID controller can be expected. Simulation study confirms that the stabilizing effect and robustness of the proposed SMES with an optimal FGS-PID controller are much superior to those of the SMES with an optimal PID controller. © 2013 ICIC International.
Keywords: Bee colony optimization; Fuzzy gain scheduling; PID controller; Power system stabilization; Superconducting magnetic energy storage